Paleohydrology of the Lower Colorado River Basin and implications for water supply availability - Lukas, Jeffrey J., author; Wade, Lisa, author; Rajagopalan, Balaji, author; Colorado Water Institute, publisher (Colorado State University. Libraries, 2012)
As the annual demand on the Colorado River system approaches the annual supply, the contribution from the Lower Colorado River Basin (LCRB)--on average about 15 percent of total system flows--becomes more critical. In order for these flows to be incorporated into planning frameworks, it is important to understand their long-term variability and develop robust simulation methods that can capture the variability. The main objectives of this project were to develop new paleo-reconstructions of LCRB hydrologic variability from tree rings and incorporate them into a more complete assessment of the risk for the entire Colorado River Basin. We first worked to develop or refine naturalized flow records for the Gila and non-Gila subbasins of the LCRB. We found that while the historic Gila River naturalized flows near the mouth could be estimated with high confidence, the non-Gila LCRB flows carry more uncertainty. We then used several different statistical methods, including two new methods, to calibrate a regional network of tree-ring data against these naturalized flow records. The resulting flow reconstructions extend back about 400 years, and are more robust for the Gila River than the non-Gila portion of the LCRB. The reconstructions show that the 20th century has been unrepresentative of the longer period of hydrologic variability in several key respects. We then incorporated the variability in these new tree-ring reconstructions into a more complete water-balance model simulating the managed Colorado River system, which was run under multiple future scenarios representing different levels of climate change impact and increasing demands. We found that the periodic large inflows from the Gila River have a small but measurable effect in reducing overall system risk (of depleting) storage under all scenarios.
October 2012.
Keywords: Gila River; tree-ring reconstruction; water shortage; reservoir levels; streamflows; Streamflow; Paleohydrology; Tree-rings -- Reconstruction; Colorado River (Colo.-Mexico); Water-supply